Left atrial appendage occlusion: What is its role today? - Abelson, M (SA Heart Journal, 2017)
In many patients with paroxysmal or permanent nonvalvular atrial fibrillation and a CHA2DS2-VASc score of 2 or more, warfarin or other newer oral anti-coagulant therapies are contra-indicated, or are not prescribed, for a variety of reasons. These patients are therefore at risk of serious life threatening thrombo-embolic events particularly large stroke. Percutaneous occlusion of the left atrial appendage, the source of the majority of these emboli, is a therapy which should be considered in these patients. There is growing evidence that this procedure is as good as, if not superior in the long term, to chronic warfarin therapy.